2021
DOI: 10.1371/journal.ppat.1009339
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 agonist, N6-LS and PGT121 delayed viral rebound in SHIV-infected macaques after antiretroviral therapy interruption

Abstract: Toll-like receptor 7 (TLR7) agonist and PGT121 (broadly neutralizing antibody, bnAb) administration previously delayed viral rebound and induced SHIV remission. We evaluated the impact of GS-986 (TLR7 agonist) and dual bnAbs on viral rebound after antiretroviral therapy (ART) interruption. Rhesus macaques inoculated with SHIV-1157ipd3N4 were initiated on daily suppressive ART from Day 14 post SHIV inoculation. Active arm animals (n = 8) received GS-986, N6-LS and PGT121 after plasma viral suppression, starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…The combination of GS-9620 with the vaccine AD26/MVA led to innate and adaptive immune stimulation, a delay in viral rebound after ART cessation, and reduced viral DNA in lymph nodes and the peripheral blood of SIV-infected monkeys [187]. Similar results were obtained in rhesus macaques infected with Simian Human Chimeric Immunodeficiency virus (SHIV), receiving GS-986 together with two bnAbs, N6-LS and PGT121, where a modest delay in the viral rebound after ART interruption was observed [188]. However, in a double-blind, multicenter, placebo-controlled trial, no changes in plasma viral loads were observed in HIV-1 positive patients under ART treated with GS-9620, despite a consistent induction in IFN response and lymphocyte activation [189].…”
Section: Innate Immunity Signaling Pathways Exploited For "Shock and ...supporting
confidence: 56%
See 1 more Smart Citation
“…The combination of GS-9620 with the vaccine AD26/MVA led to innate and adaptive immune stimulation, a delay in viral rebound after ART cessation, and reduced viral DNA in lymph nodes and the peripheral blood of SIV-infected monkeys [187]. Similar results were obtained in rhesus macaques infected with Simian Human Chimeric Immunodeficiency virus (SHIV), receiving GS-986 together with two bnAbs, N6-LS and PGT121, where a modest delay in the viral rebound after ART interruption was observed [188]. However, in a double-blind, multicenter, placebo-controlled trial, no changes in plasma viral loads were observed in HIV-1 positive patients under ART treated with GS-9620, despite a consistent induction in IFN response and lymphocyte activation [189].…”
Section: Innate Immunity Signaling Pathways Exploited For "Shock and ...supporting
confidence: 56%
“…In animal models, TLR agonists induced the expression of viral RNA, and activation of both innate and adaptive immune response [181]. These effects were further enhanced when combining the agonists with therapeutic vaccines or bnAbs [187,188]. Recently, RLRs and STING agonists have emerged as a promising new class of LRAs, with the capacity to induce the latent provirus and stimulate the selective apoptosis of reactivated cells [199].…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…They target conserved sites of vulnerability at the surface of Env: the CD4 binding site (CD4bs), the N-glycans associated with the V1/V2 and V3 loops, the silent face of gp120, the membrane proximal external region (MPER) of gp41 and a larger site spanning the interface between gp41 and gp120. In both nonhuman primates and humanized mice, infusion of bNAbs decreases viral loads 2,3 , prevents infection [4][5][6] and delays viral rebound 7,8 . Several bNAbs are under clinical evaluation 9,10 .…”
mentioning
confidence: 99%
“…ART was discontinued after antibody washout. Though TLR7 agonist and dual bnAbs delayed viral rebound by 2-fold (3 vs 6 wks, p=0.024), viral rebound occurred in all animals ( 70 ). The delay in ART initiation, the shorter duration of ART and the lower number of doses of bnAbs administered (ranging from 2-5 doses, limited by the development of anti-drug antibody) may have contributed to the reduction in efficacy when compared with the Borducchi et al.…”
Section: The Use Of Bnabs To Target Control and Potentially Eliminate The Viral Reservoirmentioning
confidence: 99%